785 Alkaline phosphatase levels in premature infants presenting with intestinal pathology. (17th August 2022) - Thomson, Emma; Khatun, Salma; Granger, Claire; Bradnock, Tim; Simpson, Judith
Abstract : Aims: Surgical necrotising enterocolitis (NEC) and spontaneous intestinal perforation (SIP) are devastating pathologies of the preterm gut. They differ histologically but clinically can be challenging to differentiate. SIP generally presents earlier than NEC, but timing of presentation can overlap. Intestinal alkaline phosphatase (ALP) secretion has been linked to gastrointestinal ischemia, and an elevated ALP at presentation has been described as a means of differentiating SIP from NEC. We describe ALP levels around presentation in a cohort of preterm infants with histologically proven SIP and NEC. Methods: We retrospectively identified preterm neonates (<32 weeks gestational age) with histologically confirmed SIP or surgical NEC cared for in our unit from 2012-2021 inclusive. We then compared serum ALP levels for the five-day period around their day of diagnosis (referred to as day 0). All statistics were run using SPSS with independent sample t-tests. Results were considered significant if p<0.05. Local Caldicott guardian approval was obtained for this work. Results: Overall, a total of 86 neonates were identified; 38 with SIP and 48 with NEC. 44 were excluded due to either missing ALP data (36) or to a change in the ALP reference range (8). This left 42 neonates; 21 with SIP and 21 with NEC. The median age at diagnosis of SIP was 6 days compared to 16 days for NEC (p<0.001). Mean ALP level was higher on day -2 in the NEC group but every day thereafter was higher in the SIP group, with the greatest rise from day -2 to day -1 i.e. 24 hours prior to diagnosis. The highest proportion of ALP levels above the reference range was on the day of diagnosis (day 0) in both groups. Table 1 and figure 1 demonstrates mean ALP levels around diagnosis, day 0. None of these differences reached statistical significance. Conclusion: Our data demonstrate a trend towards an ALP rise especially in SIP prior to clinical diagnosis, suggesting that this may have a role as an early warning sign of evolving gut pathology in some babies. Our findings are limited by small sample size and missing data but further information may be obtained from similar evaluation of larger datasets.